Rimshots : basketball pix, rolls, and rhythms - Smith, Charles R., Jr. (New York : Dutton Children's Books, 1999)
Stories and poems about playing basketball.
Wilson's Children.
Notable/Best Books (A.L.A.).
School Library Journal.
4.8
3-6
Keywords: Basketball stories; Children's stories, American; Basketball -- Juvenile poetry; Children's poetry, American; Basketball -- Fiction; Short stories; Basketball -- Poetry; American poetry; Basketball -- Fiction; Children's stories; Basketball -- Poetry; Children's poetry; Basketball -- Fiction; Short stories; Basketball -- Poetry; American poetry